A STUDY ON THE SECOND YEAR STUDENTS’ SPEAKING ABILITY AT SMA NEGERI 1 KATEMAN - Rahmayanny, Zaidatul; Gultom, Effendi; Sumbayak, Desri Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was a study on speaking ability of the second year students of SMA Negeri 1 Kateman. The aim of this study was to know about the second year students speaking ability at SMA Negeri 1 Kateman. The sample of this research was class X1 IPA 1 that consists of 13 males and 19 females. In conducting this study, there were four questions in an interview as a test which was used to know the students’ speaking ability based on five aspects: pronunciation, grammar, vocabulary, fluency, and comprehension. The questions of interview were: (1) introducing her/his self (2) telling about her/his family (3) describing the idol in her/his life (4) telling the subject her/his like in their school and its reason. To get the quantitative data in this research, the three raters were involved to give the scores of students speaking performance. From the result of the oral test in five aspects of speaking ability, the writer concluded that the average score of students’ ability in speaking from rater one it was 65.62 it was categorized as good level. From the rater two it was 66.72 it was categorized as good level. From rater three it was 67.19 it was categorized as good level. From the three raters in five aspects of speaking ability above, the average of speaking ability of students at the second year of SMA Negeri 1 Kateman was 66.51 it was categorized good level. The research finding shows that most of students were still had problems to express their idea to the listeners. It was caused by the lack of their ability in grammar, vocabulary, understanding the meaning of the word, and pronouncing the word clearly. Besides, they were lack of practice their speaking with their friend and teacher in the English classroom.Keywords : descriptive research, students’ speaking ability